Agrowaste Based Ecofriendly Bio-adsorbent for the Removal of Phenol: Adsorption and Kinetic Study by Acacia Tortilis Pod Shell - Mohammad Malakootian (Science Faculty of Chiang Mai University, 2019)
Phenolic compounds are generally organic pollutants because of their toxicity even at low concentrations and lead to many hygienic and environmental problems. In this study, Acacia tortilis as a low cost and ecofriendly bio-adsorbent was investigated for phenol removal from aqueous solutions. Adsorption study were performed in a batch system, and the effect of important operation variables including the initial phenol concentration, adsorbent dose in predetermined sizes, pH, contact time, temperature and ionic strength were evaluated. The experiments showed that the maximum efficiency capacity for phenol adsorption was above %95, which was seen at the pH of 2, adsorbent dose of 0.1 gr/l, 60-100 mesh, contact time of 10 min, temperature of 45°C and high concentration of pollutant. Also the increase in the salt concentration resulted in a decrease of phenol adsorption onto Acacia tortilis pod sell. The equilibrium data could be described well by the Freundlich isotherm equation and the kinetic studies indicated that the adsorption process was best described by the pseudo-second order kinetics. According to the results the pod shell of Acacia tortilis due to its high efficiency can act as an effective, efficient and cheap adsorbent in removal of phenol from water and wastewater.